2021
DOI: 10.1038/s41598-021-93831-3
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory function of peripheral blood CD71+ erythroid cells in systemic-onset juvenile idiopathic arthritis

Abstract: CD71+ erythroid cells (CECs) are recognized to have an immunoregulatory function via direct cell–cell interaction and soluble mediators. Circulating CECs appear in newborns or patients with hemolytic and cardiopulmonary disorders. To assess the biological role of CECs in systemic inflammation, we studied the gene expression and function in systemic-onset juvenile idiopathic arthritis (SoJIA). Peripheral blood mononuclear cells of SoJIA patients expressed upregulated erythropoiesis-related genes. It represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…We demonstrated that CECs expand in anemic patients and may suppress the production of cytokines by T cells. A small fraction of CD45 + CECs in the peripheral blood of our cohort subject is consistent with a recent report on CECs in systemic juvenile idiopathic arthritis patients 41 . In line with our results, a recent study showed that anemia status influences the blood transcriptome with enrichment of erythrocyte differentiation genes as well as ARG1 in anemic children, but decreased signatures of CD4 + T cell activation and differentiation 42 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrated that CECs expand in anemic patients and may suppress the production of cytokines by T cells. A small fraction of CD45 + CECs in the peripheral blood of our cohort subject is consistent with a recent report on CECs in systemic juvenile idiopathic arthritis patients 41 . In line with our results, a recent study showed that anemia status influences the blood transcriptome with enrichment of erythrocyte differentiation genes as well as ARG1 in anemic children, but decreased signatures of CD4 + T cell activation and differentiation 42 .…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies demonstrated that immunomodulatory properties are strong in early-stage CD45 + CECs in contrast to more mature CD45 − CECs that lack these capacities 9 , 10 , 17 , 44 . However, other studies also reported the immunomodulatory role of CD45 − CECs 41 , 45 , which suggests that CD45 alone may not be a reliable marker of immunosuppressive CECs. Here, we showed that human CECs acquire immunomodulatory properties during erythroid differentiation and are the most potent in an early stage characterized by the CD71 high CD235a mid phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…We demonstrated that CECs expand in anemic patients and may suppress the production of cytokines by T-cells. A small fraction of CD45 + CECs in the peripheral blood of our cohort subject is consistent with a recent report on CECs in systemic juvenile idiopathic arthritis patients 40 . In line with our results, a recent study showed that anemia status influences the blood transcriptome with enrichment of erythrocyte differentiation genes as well as ARG1 in anemic children, but decreased signatures of CD4 + T-cell activation and differentiation 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies demonstrated that immunomodulatory properties are strong in early-stage CD45 + CECs in contrast to more mature CD45 -CECs that lack these capacities 9,10,17,43 . However, other studies also reported the immunomodulatory role of CD45 -CECs 40,44 , which suggests that CD45 alone may not be a reliable marker of immunosuppressive CECs. Here, we showed that human CECs acquire immunomodulatory properties during erythroid differentiation and are the most potent in an early stage characterized by the CD71 high CD235a mid phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Among the immune-associated cells in the tumor microenvironment, macrophages and myeloid-derived suppressor cells play the most prominent immunosuppressive roles ( Fang et al, 2017 ; Dou and Fang, 2021 ). Furthermore, recent studies have brought a renewed focus on the immunomodulatory role of nucleated RBC ( Elahi et al, 2020 ; Kanemasa et al, 2021 ). Apart from the retention of intact nuclei, these erythroid cells display molecular features of an immature erythroid phenotype, such as high expression of the transferrin receptor protein 1 (CD71), and also express genes encoding immune checkpoint molecules, such as CD274 (encoding PD-L1) and CD244 (encoding 2B4) ( Sano et al, 2021 ).…”
Section: Nucleated Erythroid Cells: New Players In Cancer Progressionmentioning
confidence: 99%